Regulation of derepressed synthesis of arylsulfatase by tyramine oxidase in Salmonella typhimurium. - Murooka, Y (1981)
The participation of tyramine oxidase in the regulation of arylsulfatase synthesis in Salmonella typhimurium was studied. Arylsulfatase synthesis was repressed by inorganic sulfate, cysteine, methionine, or taurine. This repression was relieved by tyramine, octopamine, or dopamine, which induced tyramine oxidase synthesis, although the level of arylsulfatase activity was very low. The induction of tyramine oxidase and derepression of arylsulfatase by tyramine were strongly inhibited by glucose and ammonium chloride, and the repression of both enzymes was relieved by use of xylose as a carbon source after consumption of glucose or by use of tyramine as the sole source of nitrogen, irrespective of the carbon source used. The initial rates of tyramine uptake by cells grown with glucose and xylose were similar. Results with tyramine oxidase-constitutive mutants showed that constitutive expression of the tyramine oxidase gene resulted in derepression of arylsulfatase synthesis in the absence of tyramine. Thus, catabolite and ammonium repressions of arylsulfatase synthesis and the induction of the enzyme by tyramine seem to reflect the levels of tyramine oxidase synthesis. These results in S. typhimurium support our previous finding that the specific regulation system of arylsulfatase synthesis by tyramine oxidase is conserved in enteric bacteria.